Encyclopedia of new media : an essential reference to communication and technology - Jones, Steve, 1961- (Sage Publications, 2003)
"From ARPANET to the World Wide Web, the Encyclopedia of New Media presents more than 250 entries that explain the key terms, concepts, trends, and buzzwords that have become the everyday language of the Internet and global society. Edited by Steve Jones, one of the leading scholars in and founders of the new media field, the Encyclopedia explores the evolution and revolution in digital communications and human-computer interaction from an interdisciplinary, historical, social, and global perspective." "Featuring contributions from an international group of scholars as well as science and technology writers and editors, the Encyclopedia covers a broad spectrum. The articles are balanced between information technology and the social landscape and provide detailed descriptions and definitions of terms, covering information and communication technologies and their social contexts; pioneers, such as Marc Andreesen, Marshall McLuhan, and Steve Jobs; authors and entertainers, such as William Gibson and George Lucas; social issues, such as Privacy, Security, and Cyberwarfare; technologies, including Bluetooth, MP3, and Linux; businesses, such as Amazon.com and Napster; associations, such as the World Wide Web Consortium; and laws, such as the Communications Decency Act."--Jacket